2001
DOI: 10.1074/jbc.m108168200
|View full text |Cite
|
Sign up to set email alerts
|

Functional Analysis of Conserved Residues in the Putative “Finger” Domain of Telomerase Reverse Transcriptase

Abstract: Telomerase is a ribonucleoprotein reverse transcriptase (RT) responsible for the maintenance of one strand of telomere terminal repeats. The catalytic protein subunit of telomerase, known generically as telomerase reverse transcriptase (TERT), exhibits significant homology to RTs encoded by retroviruses and retroelements. The polymerization mechanisms of telomerase may therefore be similar to those of the "conventional" RTs. In this study, we explored the extent of mechanistic conservation by analyzing mutatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
1

Year Published

2004
2004
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 52 publications
1
21
0
1
Order By: Relevance
“…Surprisingly, we found that deletion of nucleotides 28-34 of the hTERC RNA (ie, the ⌬28-34 variant) produced similar telomerase enzymatic activity ( Figure 4A, lanes 4-6) as compared to cell lysate with either the wild-type hTERC (lanes 1-3) or the known G58A sequence polymorphism (lanes 7-9). On the contrary, other variants, which are located within either the template region (⌬52-55 and A48G) or in the known P2a paired region (⌬79C) effectively abolished telomerase enzymatic function (lanes [13][14][15][16][17][18][19][20][21], consistent with prior observations that both the template's primary sequence and the secondary structural formation of the P2a stem loop to be absolutely required for optimal telomerase enzymatic function. 3,4,39 Our results were not attributable to differences in hTERC synthesis, processing, or stability, because Northern blotting verified that each construct produced comparable steady-state levels of hTERC expression in transfected cells ( Figure 4B).…”
Section: Mutations Of Essential Template Region Of Hterc Rna Abolish supporting
confidence: 77%
See 2 more Smart Citations
“…Surprisingly, we found that deletion of nucleotides 28-34 of the hTERC RNA (ie, the ⌬28-34 variant) produced similar telomerase enzymatic activity ( Figure 4A, lanes 4-6) as compared to cell lysate with either the wild-type hTERC (lanes 1-3) or the known G58A sequence polymorphism (lanes 7-9). On the contrary, other variants, which are located within either the template region (⌬52-55 and A48G) or in the known P2a paired region (⌬79C) effectively abolished telomerase enzymatic function (lanes [13][14][15][16][17][18][19][20][21], consistent with prior observations that both the template's primary sequence and the secondary structural formation of the P2a stem loop to be absolutely required for optimal telomerase enzymatic function. 3,4,39 Our results were not attributable to differences in hTERC synthesis, processing, or stability, because Northern blotting verified that each construct produced comparable steady-state levels of hTERC expression in transfected cells ( Figure 4B).…”
Section: Mutations Of Essential Template Region Of Hterc Rna Abolish supporting
confidence: 77%
“…The other RTs (ie, P721R and T726M) showed as much telomerase activities (lanes 7-12) as did those with either the wild-type hTERT (lanes 1-3) or the known A279T polymorphic sequence 20 (lanes 19-21). Similarly, both of the remaining variants located within the C-terminal domain of hTERT (ie, R979W and F1127L) showed little to no reduction in telomerase enzymatic activities (lanes [13][14][15][16][17][18]. We also tested a novel hTERT K570N found recently in an AA patient in our cohort ( Table 1).…”
Section: Clinical Presentation and Family History Of Patients With Nomentioning
confidence: 99%
See 1 more Smart Citation
“…El motivo T y otros posibles motivos descritos como CP y CP2 parecen estar involucrados en la unión ARN -TERT (43,44). Teniendo en cuenta la conservación, al menos, del motivo T en todas las TERT, su función de unión al ARN podría ser presumiblemente compartida en todas las especies (45).…”
Section: Discussionunclassified
“…Mutations in RID2 result in a loss of telomerase catalytic activity due to lost interaction with the RNA template TER [111]. The reverse transcriptase (RT) domain is responsible for catalyzing the assembly of the telomeric DNA repeats using the TER template [113,114]. Mutations in any of its conserved aspartic acid residues ablate telomerase catalytic activity [114].…”
Section: Telomerase Reverse Transcriptase (Tert)mentioning
confidence: 99%